Stress-strain state horizontal coal seam of finite length - M.K. Kudaibergenov; A.L. Karchevsky; K.T. Iskakov (Қарағанды университетінің хабаршысы. Математика сериясы, 2018)
As the result of work, analytical expressions for calculation of tension in coal stratum of terminating length, which is under the influence of overlying breeds and is between two drifts are received. The decision is presented in the form of the sum of a polynom and a convergent series. For determination of coefficients of a row it is not required to solve the infinite systems of the algebraic equations. It promotes fast numerical finding of the required sizes with an accuracy, sufficient for practice. The given decision can be used for interpretation of data of geomechanical monitoring at combinegouge of coal in the conditions of real time and for monitoring of tension in the developed coal layer for the purpose of prediction of a possibility of mountain emission that still is very relevant problem of safety of mining operations.